Strategies to promote coping and resilience in oncology and palliative care nurses caring for adult patients with malignancy: a comprehensive systematic review. (May 2015) - Gillman, Lucia; Adams, Jillian; Kovac, Robyn; Kilcullen, Anne; House, Annita; Doyle, Claire
Executive summary : Background : Cancer care nursing is perceived as personally and professionally demanding. Developing effective coping skills and resilience has been associated with better health and wellbeing for nurses, work longevity and improved quality of patient care. Objectives : The objective of this systematic review was to identify personal and organizational strategies that promote coping and resilience in oncology and palliative care nurses caring for adult patients with malignancy. Methods : The search strategy identified published and unpublished studies from 2007 to 2013. Individual search strategies were developed for the 12 databases accessed and search alerts established. The review considered qualitative, quantitative and mixed methods studies that assessed personal or organizational interventions, programs or strategies that promoted coping and resilience. These included studies employing clinical supervision, staff retreats, psycho‐educational programs, compassion fatigue resilience programs, stress inoculation therapy and individual approaches that reduced the emotional impact of cancer care work. The outcomes of interest were the experience of factors that influence an individual's coping and resilience and outcomes of validated measures of coping or resilience.Methodological quality of studies was independently assessed by two reviewers prior to inclusion in the review using standardized critical appraisal instruments developed by the Joanna Briggs Institute. Standardized Joanna Briggs Institute tools were also used to extract data. Agreement on the synthesis of the findings from qualitative studies was reached through discussion. The results of quantitative studies could not be statistically pooled given the different study designs, interventions and outcome measures. These studies were presented in narrative form. Results : Twenty studies were included in the review. Ten studies examined the experience of nurse's caring for the dying, the emotional impact of palliative care and oncology work and strategies to prevent burnout or avoid compassion fatigue, challenges in self‐care, and processes nurses adopted to cope with work related stress. Six studies evaluated different interventions provided by organizations to improve coping and resilience. Evidence for the effectiveness of interventions was limited to three studies. The results are discussed under four headings: (i) preventative measures (ii) control measures (iii) unburdening and "letting go", and (iv) growing and thriving. Conclusion : This review identified a number of strategies to better prepare nurses for practice and maintain their psychological wellbeing. Although no firm conclusions can be drawn in respect to the most effective interventions, strategies with merit included those that: a) foster connections within the team; b) provide education and training to develop behaviors that assist in controlling or limiting the intensity of stress, or aiding recovery; and c) assist in processing emotion and learning from experiences. Although individuals must take responsibility for developing personal strategies to assist coping and resilience, organizational support is integral to equipping individuals to deal with work related challenges. Implications for practice A range of formal and informal support is required to promote coping and resilience. Implications for research There is a need for large, well designed, multisite, experimental studies to evaluate the effectiveness of interventions that promote coping and resilience in adult palliative care or oncology nurses.